2008
DOI: 10.1002/jms.1459
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic‐energy‐sensitive mass spectrometry for separation of different ions with the same m/z value

Abstract: A double-focusing mass spectrometer (MS) equipped with a superconducting-tunnel-junction (STJ) detector has been applied to measure relative ionization cross-sections for the production of ions that are accompanied by different ion species with the same mass-to-charge (m/z) value. The STJ detector fabricated for this study enables kinetic energy (E) measurement of incoming individual ions at a counting rate of up to approximately 100 k ions/s and an energy resolution (DeltaE/E) of 15%. Both high counting rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…5, where the contribution from each distribution to the m/q = 14 or 15 products, relative to 14,15 N 2 + , are shown as a function of the electron energy. The measured ratios between the cross section associated with each of the energy distributions and the cross section of the parent molecule for ions with m/q = 14 and m/q = 15 are given in Tables I and II, [27,28] and with the homoisotopic 14 N 2 measurement of Shiki et al [16] at 70 eV, with very good general agreement. To the authors' knowledge, besides Ref.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…5, where the contribution from each distribution to the m/q = 14 or 15 products, relative to 14,15 N 2 + , are shown as a function of the electron energy. The measured ratios between the cross section associated with each of the energy distributions and the cross section of the parent molecule for ions with m/q = 14 and m/q = 15 are given in Tables I and II, [27,28] and with the homoisotopic 14 N 2 measurement of Shiki et al [16] at 70 eV, with very good general agreement. To the authors' knowledge, besides Ref.…”
Section: Resultsmentioning
confidence: 58%
“…To the authors' knowledge, besides Ref. [16], which uses a cryogenic detection system, there are no other previous measurements reporting the N 2 2+ /N 2 + ratio for homoisotopic species. For a consistency verification, the sum of all ratios (total) for 14 N 2 is compared to the single-coincidence measurements of Tian and Vidal [29], also showing very good agreement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 A technical description and review of STJs may be found elsewhere. [45][46][47] Use of STJ detection at 1 MTh and higher have been reported for IgM (~1 MDa) 48 and polystyrene (~2 MDa) 49 50,51 Signal responses from a more typical ionizing detector, such as a microchannel plate (MCP) detector, coupled to a typical MALDI-TOF instrument would not achieve the S/N level required to be useful for most analyses at these high m/z.…”
Section: Introductionmentioning
confidence: 97%
“…1 that the ions of C60 + and C60 ++ are clearly separated according to the deposited energies, which ensures that charge state discrimination for individual ions is possible. After eliminating the secondary peaks, the charge state discrimination enables separation of doubly-charged homonuclear diatomic molecule ions ( 14 N ++ 2 ) from singly-charged atomic ions ( 14 N + ) for the first time [10]. Both of 14 N ++ 2 and 14 N + have the same m/z of 14, so that any conventional MS instruments are unable to distinguish these two ionic species.…”
Section: Resultsmentioning
confidence: 99%